Tool wear monitoring in single-point diamond turning using laser scattering from machined workpiece. (January 2018) - Hocheng, H.; Tseng, H.C.; Hsieh, M.L.; Lin, Y.H.
Abstract: In ultra-precision machining, diamond turning is widely applied for optical components and die cores. When operating diamond turning, the tool wear is among the most significant concerns, which causes the deterioration of machining quality and the waste of material and time. The tool wear is unable to be assessed by naked eyes, a tedious off line measurement is employed for evaluating the tool wear. In this paper, an optical method using laser-light scattering to evaluate the tool wear is proposed for maintaining the machining quality and determining the appropriate timing for tool change while manufacturing light guide plate. In this optical method, the progress of the tool wear of nose radius is monitored by the scattered light beams from the machined surface. The incident angle between 20 and 30 degrees is found to provide the best results for monitoring the tool wear.